Control Strategy for PWM Voltage Source Converter Using Fuzzy Logic for Adjustable Speed DC Motor - Saidah Baisa; Bambang Purwahyudi; Kuspijani Kuspijani (Institute of Advanced Engineering and Science, 2017)
The speed of a DC motor can be controlled by varying the voltage applied to the terminal. It can be done by controlling a PWM-VSC (PWM-Voltage Source Converter). This paper analyzes an control strategy of PWM-VSC using fuzzy logic to obtain varying DC voltage and according to the DC motor speed as desired. The control strategy of PWM-VSC directly using the switch variable in dq rotating reference frame as input variables. The fuzzy logic controller proposes to get a DC voltage variation stable by adjusting amplitudo of the network current. The simulation Fuzzy Logic Controller results show that the design fuzzy logic produce a good dynamic of DC voltage and DC motor speed without overshoot. On the network, Total Harmonic Distortion less than 5 % and unity power factor.